Selection and application of methanol-utilizing bacteria from tomato leaves for biocontrol of gray mold - Suenaga, Hiroyuki; Hira, Tomoko; Yoshimura, Takahiro; Oka, Takuji; Hira, Daisuke (Frontiers in Microbiology, 2024)
Gray mold, caused by Botrytis cinerea, is a significant threat to tomato production. Traditional chemical control methods have become increasingly ineffective because of the development of resistance. This study aimed to isolate methanol-utilizing bacteria from tomato leaves and evaluate their biocontrol potential against gray mold. To obtain bacterial suspensions, tomato leaf samples were collected and washed. We analyzed the microbial communities of these samples using 16S rRNA amplicon sequencing and identified several methylotrophic strains. Among these, 405 isolated strains were cultivated on a solid low-nutrient inorganic salt medium containing methanol, and 7 strains exhibiting considerable antifungal activity against B. cinerea were identified. Greenhouse tests revealed that two strains-SY163 and SY183-significantly reduced the severity of gray mold on tomato leaves. Disease index scores and the area under the disease progress curve values confirmed the efficacy of these strains as biocontrol agents. Statistical analysis indicated the effectiveness of pre-and co-application of these strains with B. cinerea. Phylogenetic analysis identified Serratia rubidaea as the inhibitory strain. The biocontrol activity is likely mediated through the production of antifungal compounds and suppression of B. cinerea sporulation. This study provides the basis for developing a technology of gray mold suppression by controlling the abundance of S. rubidaea in plant microbial communities.